STUDY ON VOCABULARY LEARNING STRATEGIES USED BY HIGH ACHIEVERS OF ENGLISH EDUCATION DEPARTMENT OF UNIVERSITY OF ISLAM MALANG - Nadya Ramadhanty Fauzia; Yahya Alaydrus; Dzul Fikri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This article aims to describe the vocabulary learning strategies used by high achievers. The research design used in this research is descriptive qualitative. The subjects in this study were fourth semester students who were high achievers in the English Education Department. The subjects in this study were 10 students. To collect data in this study, the researcher using questionnaires to get validity of the data and interviews as supporting instruments. The questionnaire consisted of 25 multiple choices which included 6 kinds of vocabulary learning strategies according to Oxford (1990). The results of this study are high achievers using memory, cognitive, compensation, metacognitive, affective, and social strategy in learning vocabulary. Meanwhile, the strategy most often used by high achievers is the compensation strategy. The researcher offer suggestion as follows: 1) For teacher, this research can provide information related to various strategies in learning vocabulary so that it can be used to improve vocabulary skills in students also it can facilitate the teaching and learning process. 2) For students, the students are suggested to use more strategy in learning vocabulary especially compensation strategy. 3) For readers, this research can help readers to increase knowledge about vocabulary learning strategies. 4) For the other researchers, this research can be a reference and can help other researchers to develop similar research so that it is expected to find new findings from the research conducted.Key words: High achievers, advanced vocabulary, vocabulary learning strategies